Attentional contributions to children’s limited visual short-term memory capacity: developmental change and its neural mechanisms - Shimi, A (2012)
It is increasingly recognised that, in adulthood, attentional control plays an important role in optimising the ability to encode and maintain items in visual short-term memory (VSTM). Memory capacity limits increase dramatically over childhood, but the mechanisms through which children guide attention to maximise VSTM remain poorly understood. Through a number of experiments manipulating different parameters, the current thesis aimed to explore the developmental trajectories of the neurocognitive mechanisms underlying selective attention within VSTM and to examine whether variations in attentional control are accompanied by individual differences in VSTM capacity. Chapters 2 and 3 investigated the development of attentional orienting in preparation for encoding and during maintenance. Younger children emerged as less able than older children and adults to orient attention to internally held representations. Therefore, Chapter 4 tested whether younger children’s attentional orienting is differentially affected by memory load. While attentional orienting prior to encoding was more beneficial when required to remember a greater number of items, cueing benefits during maintenance were similar across load conditions. Chapter 5 investigated whether temporal parameters influence younger children’s variable ability to orient attention during maintenance. Attentional orienting operated more efficiently on transient iconic traces rather than on VSTM representations due to passive decay of the memory traces as a function of time. Chapter 6 assessed whether the characteristics of the memoranda constrain the efficiency of attentional orienting within VSTM. Attentional orienting supported differentially the maintenance of familiar and meaningless items and pinpointed the quantitative improvement of mnemonic strategies over development. Finally, Chapter 7 examined the temporal dynamics of prospective and retrospective orienting of attention in VSTM. Children deployed neural pathways underpinning attentional orienting less efficiently than adults and differentially across the two orienting conditions suggesting their neural dissociation. Overall, findings from the current thesis define how children develop the ability to deploy attentional control in service of VSTM.